Reversible data hiding scheme based on asymmetric histogram modification - Zhiheng LYU; Lei LIU; Si CHEN; Zhaoxia YIN (网络与信息安全学报)
A reversible data hiding scheme was improved,using two different forecast methods to calculate the prediction error of the original image,two asymmetric prediction error distribution histogram generated,when making secret information embedded respectively on two asymmetric prediction error distribution histogram in the opposite direction of translation ways.Compared with the traditional scheme,the improved scheme can play better to the complementary advantages of embedding strategy,make as many pixels pixel values compensation occur,further protecting the secret image quality.